2005
DOI: 10.1038/sj.sc.3101802
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of muscular and articular factors in the progression of contractures after spinal cord injury in rats

Abstract: Study design: Experimental, controlled trial. Objectives: To identify the relationship between the muscular and articular factors in the progression of contractures after spinal cord injury (SCI). Setting: Hiroshima University, Hiroshima, Japan. Methods: In total, 48 female Wistar rats were used. The 24 experimental rats that underwent a spinal cord transection and the other 24 control rats that underwent a sham-operation were assessed at 2, 4, 8, 12, 16, or 24 weeks postsurgery. Knee joint motion was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 36 publications
2
36
0
Order By: Relevance
“…combined arthrogenic and myogenic restriction at first measurement, and then, arthrogenic restriction was measured after resection of the periarticular muscles Moriyama et al 2006). In these methods, arthrogenic structures may be damaged at the first measurement, which influenced the second measurement of the arthrogenic component (Trudel et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…combined arthrogenic and myogenic restriction at first measurement, and then, arthrogenic restriction was measured after resection of the periarticular muscles Moriyama et al 2006). In these methods, arthrogenic structures may be damaged at the first measurement, which influenced the second measurement of the arthrogenic component (Trudel et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The factors responsible for joint contracture are mainly divided into the muscles (myogenic) and the periarticular structures (arthrogenic) (Evans et al 1960;Enneking and Horowitz 1972;. Recent studies indicated that the arthrogenic factors, especially the joint capsule, played an important role in the progression of limited range of motion after immobilization Moriyama et al 2006;Lee et al 2010). We revealed in the previous report that the arthrogenic limitation occurred after a 4-week immobilization in a rat immobilized knee model and the restricted motion was restored after incision of the capsule, which indicated that the joint capsule was one of the most responsible factors of limited range of motion after immobilization (Chimoto et al 2007).…”
mentioning
confidence: 99%
“…[5][6][7]9 The eight SCI animals were anesthetized by intraperitoneal administration of 40 mg kg À1 sodium pentobarbital. After the spinal cord was exposed by a laminectomy of the T8 vertebra, it was completely transected at the level of T8.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Rectangles (30 mm deep and 400 mm long) were superimposed to the superficial and deep cartilage. Intense [5][6][7] Therefore, the FA cartilage corresponds to unapposed regions (no contact between cartilage surfaces) of the flexed knee. The FP, TA and TP regions are located at apposed regions (where the articular cartilages of two bones contact each other).…”
Section: Tissue Preparation and Stainingmentioning
confidence: 99%
See 1 more Smart Citation